THE TYRANNY OF TESTS: DOING AWAY WITH TESTS WITHOUT SELLING YOUR SOUL TO GRADING HELL. Issue 2 (3rd April 2019) - Mittal, Sarah
Abstract : This innovation proposes an alternative to the traditional exam/test model. Many faculty members have likely struggled with the need to objectively assess their students and the push back they get from students in administering such assessments. The current article outlines a win-win solution that allows professors to objectively assess student performance, while reducing anxiety, inducing increased preparation for class, and encouraging higher engagement during class activities and lectures—all without becoming a slave to subjective grading assignments. It blends three key elements: numerous quizzes, hand-written notes, and the use of an app-based technology to administer and grade the assessments.